Implementing Speaking Skills Instruction in Islamic Institutes in Probolinggo - Islamy, Mohammad Fadil Akbar (JURNAL IJ-ATL, 2022)
This study aims to examine the implementation of teaching speaking skills at two Islamic institutes in Probolinggo: the Nurul Jadid Institute and the Al-Masdouqiya Institute. The objectives of this research are to analyze the methods and approaches applied to enhance students' fluency and adherence to grammatical rules in speaking Arabic. This research employs a qualitative approach with a descriptive method, utilizing observation, interviews, and document analysis as data collection tools. The findings indicate that both institutes emphasize similar objectives: training students to speak Arabic fluently and accurately. At the Nurul Jadid Institute, the instructional content includes vocabulary, dialogue, scientific discussion, public speaking, storytelling, news reading, and grammar. The instructional methods applied involve memorization, direct interaction, and the oral-aural method. Instructional materials and tools include books such as Modern Dialogue, Al-Jarumiyyah, Al-Amriti, Al-Alfiyyah, and morphological examples, as well as blackboards and projectors. Evaluation consists of weekly, formative, and summative assessments conducted on a semester basis. Similarly, at the Al-Masdouqiya Institute, instructional content encompasses vocabulary, dialogue, lectures, reading, and grammar, while the methods also incorporate memorization, direct methods, and the oral-aural approach. Materials include daily vocabulary books, clear grammar and morphological examples, a blackboard, and a projector. Evaluation follows the same frequency and structure as at the Nurul Jadid Institute. The study contributes insights into the structured approaches to teaching speaking skills at Islamic institutes and highlights the instructional methods and materials that can effectively support Arabic fluency and comprehension in a structured, outcome-focused manner.